Factor analysis of fermentation for the production of biopolymer in shake-flasks - Nafsiah , Hussain (2008)
Poly( ß- hydroxybutyric acid ) or (PHB) is a natural, biodegradable polymer, which is accumulated as an energy reserve material by a large number of bacteria when nutrient such as nitrogen source is available in limiting concentrations in the present of excess carbon source. The major problem associated with the industrial production of PHB is its high production cost. In the present study, effort was made to screen out the factors of the experiment that influence the production of biomass that is Cupriavidus necator and also PHB. The factors was including culture media such as glucose, CaCl2.2H2O, trace element, (NH4)2SO4 and Na2HPO4.7HO agitation and temperature. Matlab and F-Test distribution have been use to screen out insignificant factor. These factors can then be classified into categories according to how significantly each of them affects the yield. If experimental variable contribute only to factors do not affect the yield significantly then it can be concluded that it is not relevant to the yield and can be dropped from subsequent experiments. If an experimental variable contributes to one or more factors which have significant effects on the yield then the experimental variables is relevant to the yield and should be retained for future investigation an optimization. -Author